Down Syndrome: how to communicate the diagnosis - Caterina Gori; Guido Cocchi; Luigi Tommaso Corvaglia; Giuseppe Ramacieri; Francesca Pulina; Giacomo Sperti; Valeria Cagnazzo; Francesca Catapano; Pierluigi Strippoli; Duccio Maria Cordelli; Chiara Locatelli (BMC, 2023)
Abstract Communicating the diagnosis of Down Syndrome to a couple of parents is never easy, whether before or after birth. As doctors, we must certainly rely on our own relational skills, but it is also necessary to be confident in some general indications, which are often overlooked in the strict hospital routine. This article is intended as a summary of the main articles published on this subject in the international literature, collecting and summarising the most important indications that have emerged in years of medical practice all over the world as well as in our personal experience. The diffusion of these guidelines is essential to help the doctor in this difficult task, on which there is often little training, and above all to guarantee to the parents the least traumatic communication possible.